COMMUNICATION STRATEGY OF THE NATIONAL COUNTER TERRORISM AGENCY IN THE DERADICALIZATION PROGRAM IN INDONESIA - Sugiarto, Sugiarto (Jurnal Pertahanan dan Bela Negara, 2020)
The National Counter Terrorism Agency (BNPT) said that until the end of 2018 the success rate of the deradicalization program reached one hundred percent. The deradicalization program has already been attended by 800 people; 325 former terrorism inmates and the rest of the families of terrorist prisoners. None of the 325 ex-terrorist inmates who participated in the deradicalization program resumed acts of terror. One aspect that supports the success of the deradicalization program in Indonesia is the communication aspect. The purpose of this study is to elaborate aspects of communication, especially BNPT communication strategies in the deradicalization program. The author uses qualitative research methods in this study. The conclusion of the research shows that BNPT utilizes the communication strategy as one of the successes of the success of the deradicalization program even though the communication strategy used by the BNPT is not written and detailed. Keywords: communication, a former terrorist convict, strategy, deradicalization, terrorism.